2011
DOI: 10.1158/1535-7163.mct-10-1091
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Activity of Gemcitabine and ABT-737 In Vitro and In Vivo through Disrupting the Interaction of USP9X and Mcl-1

Abstract: The Bcl-2 antagonist ABT-737 targets Bcl-2/Bcl-xL, but not Mcl-1, which may confer resistance to this agent in various cancers with high levels of Mcl-1. Here, we showed that the combination of gemcitabine and ABT-737 exhibited synergistic cytotoxicity and induced significant apoptosis in multiple cancer types, including lung, renal, bladder, and prostate cancers. The enhanced apoptosis induced by gemcitabine plus ABT-737 was accompanied by the greater extent of mitochondrial depolarization, caspases-3 activat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 48 publications
4
36
0
1
Order By: Relevance
“…In our study, decreased XIAP expression was detected in A549 cells treated with chamaejasmenin B, indicating that apoptosis suppression was impaired. Mcl-1 is an essential modulator of survival during development and maintenance in a variety of cell lineages and is a key regulator of apoptosis after DNA damage [31,32] . Our data showed that chamaejasmenin B-induced apoptosis was accompanied by a large decrease in Mcl-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, decreased XIAP expression was detected in A549 cells treated with chamaejasmenin B, indicating that apoptosis suppression was impaired. Mcl-1 is an essential modulator of survival during development and maintenance in a variety of cell lineages and is a key regulator of apoptosis after DNA damage [31,32] . Our data showed that chamaejasmenin B-induced apoptosis was accompanied by a large decrease in Mcl-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that high levels of Mcl-1 may confer resistance to ABT-737 in several solid tumors (17). Thus, the present study examined the involvement of Mcl-1 in nedaplatin and ABT-737 combination treatment.…”
Section: Combination Of Nedaplatin and Abt-737 Promoted The Degradatimentioning
confidence: 92%
“…Thus, it was hypothesized that low expression of Mcl-1 contributed to the synergistic effect in cancer cell lines. As in all proteins, the equilibrium between production and degradation determines the protein level of Mcl-1, and the stability of Mcl-1 could be critically important in numerous physiologic and pathologic situations (17). Firstly, it was postulated that the synergistic reduction of Mcl-1 protein by nedaplatin plus ABT-737 was the result of transcriptional inhibition.…”
mentioning
confidence: 99%
“…Increased USP9X expression should correlate with increased MCL1 protein in tumors and is expected to have a survival advantage. Interestingly, it was shown that inhibiting USP9X to decrease MCL1 potentiates ABT-737 [95,96], further suggesting its role in determining ABT-737 (and navitoclax) sensitivity.…”
Section: Future Directions In Developing Biomarkers Of Response To Anmentioning
confidence: 99%